Modelling drivers of adapt for effective strategy execution. Issue 6 (2nd September 2014) - Kumar Srivastava, Amit; , Sushil
Abstract : Purpose: – The purpose of this study is to develop a framework for "Adapt" in the context of strategy execution. Design/methodology/approach: – Both exploratory and confirmatory modes of research using Confirmatory Factor Analysis, Interpretive Structure Modeling, Total Interpretive Structural Modeling and t -test methods have been conducted. Findings: – The conceptualization of learning and learning organization can only be possible when organization develops adaptive culture. When an organization becomes learning organization, it starts becoming vital by adopting flexibility wherever and whenever it is required. This vitalization process helps organization use successfully the frameworks of strategy execution. Research limitations/implications: – In many cases the Balance Score Card could not succeed. Our study suggests that the adaptive culture gives impetus for learning and growth suggested in balanced scorecard (BSC) and adapt suggested in Management System. This study is more an exploratory effort with limited sample size. The findings can be consolidated and enriched with significantly large sample from varied contexts. Practical implications: – There is clear relative importance and sequence of corrective actions required to improve the hit rate of strategy execution. Organization can use the proposed framework to handle the issues of adapt in strategy execution. Originality/value: – Many scholars have pointed out that there is lack of strategy execution framework, and more specifically, in the case of adapt. The study contributes by providing a conceptual framework to address different aspects of adapt and change management for effective strategy execution. Additionally, this study adds methodological value to traditional model building.